Factors Related to the Intention to Cigarette Smoking among Junior High School Students in Jatinangor Subdistrict, West Java - Yee, Ngu Ling; Sunjaya, Deni Kurniadi; Karyono, RM Haryadi (Althea Medical Journal, 2015)
Background: Cigarette smoking is known to harm the health of smokers and causes the death of millions people around the world. Smoking initiation in Indonesia is begun early especially during teenagers year. The aim of the study was to analyze the factors related to the intention to cigarette smoking among Junior High School students in Jatinangor subdistrict.Methods: A quantitative method with cross sectional study was conducted in the junior high school setting during the period of September to November 2013. Inclusion criterias were students aged 13Â15 years old and did not smoke. Four factors were measured in this study, which were attitudes toward cigarette smoking, parents who smoke, peers influence and advertisement where each factor had 5 questions with âYesâ or âNoâ answers. Data were collected through self-administered questionnaire among 226 students using stratified random sampling. Statistical analysis of the variables was using chi square test.Results: As much as 44.25% of the respondents had intention and 55.75% had no intention to cigarette smoking. This study showed significant relation among attitudes, parents who smoke, peers influence and advertisements with the intention to cigarette smoking.Conclusions: Half of the respondents have intention to cigarette smoking and the most factors related to it are peers influence.Â DOI:Â 10.15850/amj.v2n3.528